An analysis of the legal uncertainty of subject matter in trust in Malaysia & with reference to the legal position in England / Beatrice Minda Winston Bale, Hafizah Rozlan, Wan Nor Idayu Wan Jusoh - Winston Bale, Beatrice Minda; Rozlan, Hafizah; Wan Jusoh, Wan Nor Idayu (2011)
The researcher wants to study about the legal uncertainty in trust in Malaysia with the reference to the legal position in England. The researchers intended to compare and contrast trust cases in different jurisdiction with current position in Malaysia and learn lessons from it. In addition, the researchers also compare and contrast scholars' opinion on the issue of certainty of subject matter in trust. The researchers also interviewed three respondents in obtaining their views on this matter. The researchers had conducted qualitative techniques. For the first method, the researchers had conducted a library based research from various books, statutes and articles. Based on this research, the researchers had compare and contrast the scholars' opinion. On the second method, the researchers had conducted a semi-structured interviews to obtain views relating our main research question. The interview aimed to provides the researchers with a better understanding and knowledge on the concept of the certainty of subject matter. The last approach is through comparative case study in which the researchers gathered relevant cases from England, Australia, New Zealand and Malaysia from the earliest to the latest and the researchers will examine the principles applied in determining the certainty of subject matter. Through this research, the researchers had learnt a lot about the approaches taken by the Court in different jurisdictions and how they indulged in their freedom of discretion. Through this research, the researchers had developed more understanding about the legal uncertainty of subject matter in trust based on England position. In conclusion, we have found that Malaysian position in trust in the context of certainty of subject matter is a mixture of two approaches i.e. the liberal and strict approach.